Evolving Work Routines: Adaptive Routinization of Information Technology in Healthcare - Goh, Jie Mein; Gao, Guodong (Gordon); Agarwal, Ritu (Information Systems Research, 2011)
Despite the significant potential for performance gains from health IT (HIT), there has been limited study of the mechanisms underlying successful HIT implementations. We conducted an extensive longitudinal field study to gain an understanding of the interplay between technology and patterns of clinical work embodied in routines. We use the analytical device of narrative networks to identify where and how HIT influences patterns of work. We further draw upon adaptive structuration theory to conceptualize HIT as an intervention that alters the flow of events in a narrative network. Our findings suggest that the key to successful implementation is to manage the co-evolution process between routines and HIT and to actively orchestrate a virtuous cycle through agentic action. We propose a dynamic process model of adaptive routinization of HIT that delineates the major channels through which HIT and routines interact, identifies the different stages in the dynamic co-evolution process, and isolates the pivotal role of two forms of agency in enabling the virtuous cycle of co-evolution. This is one of the first studies to offer a processual, microlevel analysis of HIT implementation in a clinical setting.